Penguatan Fungsi Pengawasan Bawaslu Republik Indonesia dalam Penyelenggaraan Tahapan Kampanye Pemilu Serentak 2024 - Nasution, Ali Imran; Azaria, Davilla Prawidya; Fauzan, Muhammad; Abidin, Fikri Rafi Musyaffa; Alfarissa, Tiara (Universitas Serang Raya, 2023)
One of the stages in a general election is the campaign. During the campaign stage, there is an institution that has the authority to supervise it, namely Bawaslu RI. However, in its implementation, Bawaslu RI experienced several challenges, especially in facing the simultaneous elections in 2024, such as a lack of human resources, financing and facilities for supervision. The research method used is normative juridical with a statutory approach and a conceptual approach. The results of the research show that Bawaslu RI is affected by the implications of 2024 simultaneous elections, such as shortages of human resource and technical needs in the field with a solution by changing the Article 92 paragraph (2) of Law No.7/ 2017 to change the number of Bawaslu RI members from each existing level. Then, the strategy of Bawaslu RI in supporting its supervisory authority during simultaneous elections is to collaborate with various institutions such as the implementation of Gakkumdu, as well as entering into an MoU with Kominfo, KPU, and all social media in Indonesia.